To the knowledge of Hedychridium Abeille de Perrin, 1879 (Hymenoptera: Chrysididae) of Mediterranean Region, with description of new species and new synonymy - Strumia, Franco (Zootaxa, 2012)
New species Hedychridium goloensis Strumia, sp. nov. from Western Mediterranean Region is described and figured. New synonymy is proposed for Hedychridium jucundum Mocsàry, 1889 (=Hedychridium reticulatum hyalitarse Perraudin 1978, syn. nov.). The number of Hedychridium species known for Sardinia and Corsica increased to 15 and 17 respectively.